2018
DOI: 10.1039/c8ra07039c
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in microbial community structure and diversity in a novel waterfall biofilm reactor combined with MBBR under light and dark conditions

Abstract: In this study, a novel, low-cost, easy-maintenance and effective waterfall aeration biofilm reactor (WFBR) was designed to treat wastewater with MBBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Continuous addition of 2 mM Fe(III) resulted in a reduction of sulfide concentration by about 0.9 mM and no significant changes in total iron loss. The total iron concentration in the solution was about 14 mM, which was close to the total iron concentration studied by Zhang et al [36]. Considering that the addition of Fe(III)EDTA would increase the loss of total iron and the inhibition of EDTA on microorganisms, the Fe(III)EDTA concentration no longer increased and was maintained at 6 mM.…”
Section: Simultaneous Biological and Chemical Removal Of Sulfate And supporting
confidence: 83%
“…Continuous addition of 2 mM Fe(III) resulted in a reduction of sulfide concentration by about 0.9 mM and no significant changes in total iron loss. The total iron concentration in the solution was about 14 mM, which was close to the total iron concentration studied by Zhang et al [36]. Considering that the addition of Fe(III)EDTA would increase the loss of total iron and the inhibition of EDTA on microorganisms, the Fe(III)EDTA concentration no longer increased and was maintained at 6 mM.…”
Section: Simultaneous Biological and Chemical Removal Of Sulfate And supporting
confidence: 83%
“…The DNR also increases with a higher OLR. In a previous study [25,26], a high concentration of influent COD (2000 mg/L) also resulted in nearly 100% TN removal [25]. Overall it can be concluded that the WABR is a simple but efficient reactor for COD and N removal.…”
Section: Impact Of Olr On Cod and N Removalmentioning
confidence: 75%
“…COD, ammonium and total phosphorus (TP) were measured spectrophotometrically according to standard methods [43] using HACH test kits and a DR 3900 VIS Spectrophotometer [26]. Nitrite and nitrate were measured by Dionex ICS-900 Ion Chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations